2004
DOI: 10.1002/chin.200503190
|View full text |Cite
|
Sign up to set email alerts
|

Thio Arsenosugars Identified as Natural Constituents of Mussels by Liquid Chromatography‐Mass Spectrometry.

Abstract: Carbohydrates U 0500Thio Arsenosugars Identified as Natural Constituents of Mussels by Liquid Chromatography-Mass Spectrometry. -Two novel thio arsenosugars (II) are identified by LC-MS coupling and independent synthesis from the corresponding arsine oxides (I). -(SCHMEISSER, E.; RAML, R.; FRANCESCONI*, K. A.; KUEHNELT, D.; LINDBERG, A.-L.; SOEROES, C.; GOESSLER, W.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…However, there are at least 40 minor arsenic species [58]. Recently two new classes of arsenic species, the thioarsenic species where the 'O' bonded to As is replaced by an "S" and arsenic lipids (arsenic hydrocarbons and arsenophospholipids) have been discovered increasing the complexity of arsenic species that exist in marine organisms [59].…”
Section: Arsenic In Seaweeds Mollusks Crustaceans and Fishmentioning
confidence: 99%
“…However, there are at least 40 minor arsenic species [58]. Recently two new classes of arsenic species, the thioarsenic species where the 'O' bonded to As is replaced by an "S" and arsenic lipids (arsenic hydrocarbons and arsenophospholipids) have been discovered increasing the complexity of arsenic species that exist in marine organisms [59].…”
Section: Arsenic In Seaweeds Mollusks Crustaceans and Fishmentioning
confidence: 99%
“…This procedure oxidized thio-arsenosugars to oxo-arsenosugars, allowing quantification of the thio-arsenosugars by difference. [36] Oxidation of As(III) to As(V) occurrs simultaneously by this method.Reverse phase chromatography using a Shisheido Capcell PAK C18 MGII (4.6 mm × 250 mm, 5 μm, Shiseido Co., Ltd., Tokyo, Japan) with a mobile phase of 10 mM sodium 1-butansulfonate, 4 mM tetramethylammonium hydroxide, 4 mM malonic acid, 0.5% methanol at pH 3, with a flow rate of 1.0 mL min −1 [37] was used for separation of co-eluting unknown organic arsenic species.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure oxidized thio-arsenosugars to oxo-arsenosugars, allowing quantification of the thio-arsenosugars by difference. [36] Oxidation of As(III) to As(V) occurrs simultaneously by this method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, thiol-organoarsenic species, including DMDTA V and DMMTA V , have been reported in a wide range of systems, such as in marine algae [13], vegetation [14], mussels [15], animals [2,[16][17][18][19], and human beings [20,21]. Ochi et al [4] and Naranmandura et al [22] suggested that biologically generated sulfide (HS − ), glutathione (GSH), or sulfide coordinated with a monothiol (protein-S-SH) or dithiol group (protein-S-S-S-protein) may be involved in biological arsenic transformation.…”
Section: Introductionmentioning
confidence: 99%